Comprehensive textbook on foundation of nursing-I - Nissanka (Jadhav), Rebecca (New Delhi : Jaypee Brothers Medical Publishers, 2025)
Designed according to the INC syllabus for Nursing Foundation-I (Semester I), this textbook provides theoretical and practical coverage of nursing principles, components, and techniques, focusing on cognitive, affective, and psychomotor skills.
Keywords: Nursing -- Foundations; Nursing -- Education